2022
DOI: 10.22541/au.166299845.50808480/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White Sponge Nevus of the Oral Cavity: Affecting Members of Two Generations in a Family

Abstract: White sponge nevus (WSN) /Canon’s disease is a rare, autosomal dominant mucosal disorder. WSN falls in the category of Oral Genodermatosis which can be easily diagnosed based on the history and clinical examination. Here we report the first two cases of WSN in a young girl and her mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The autosomal dominant feature of this disease is irregular penetrance, variability, and expressivity within the same family [3][4][5]. No similar lesions were found among the patient's relatives, and the lesions only affected the oral mucosa.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The autosomal dominant feature of this disease is irregular penetrance, variability, and expressivity within the same family [3][4][5]. No similar lesions were found among the patient's relatives, and the lesions only affected the oral mucosa.…”
Section: Discussionmentioning
confidence: 94%
“…In white sponge nevus, point mutations involve the keratin four and keratin 13 genes, which encode the mucosa-specific keratin intermediate filament proteins cytokeratin 4 (type 2) and cytokeratin 13 (type 1). These proteins are important for the formation of keratin filaments [4,5]. Liu et al compared sporadic and familial cases of white spongiform nevus and concluded that only one in five sporadic cases had keratin mutations [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations